2018
DOI: 10.1111/1750-3841.14217
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Phenolic Compounds and Lipase: The Influence of Solubility and Presence of Particles in the IC50 Value

Abstract: Obesity is one of the principal human health problems and one of the main treatments against it is the inhibition of pancreatic lipase, the main responsible enzyme of lipid digestion. For that purpose, previous studies have tested several phenolic compounds against lipase, without considering their aggregation behavior in aqueous solutions. Because of this, the present study focuses on understanding how the solubility and the presence of particles affect the IC value of the interaction between lipase and pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 27 publications
5
20
0
Order By: Relevance
“…The increased optical density displayed in Figure 1 shows that myricetin can form aggregates in aqueous solutions, as reported previously (26) and that the optical density increases with increasing myricetin concentration. For the data obtained in water,it is possible to see that for 600 and 1000 µM of myricetin, there is a significant change in the optical density (with respect to the blank), indicating that after two hours myricetin aggregates were detected at those concentrations.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The increased optical density displayed in Figure 1 shows that myricetin can form aggregates in aqueous solutions, as reported previously (26) and that the optical density increases with increasing myricetin concentration. For the data obtained in water,it is possible to see that for 600 and 1000 µM of myricetin, there is a significant change in the optical density (with respect to the blank), indicating that after two hours myricetin aggregates were detected at those concentrations.…”
Section: Resultssupporting
confidence: 86%
“…From table 2 we can see that the size of the small myricetin aggregates is in the range of a few nm. Large myricetin aggregates were previously detected by dynamic light scattering (DLS) (26, 29), but the use of separation with AF4 allowed for the detection of smaller myricetin aggregates without the interference of large aggregates. The myricetin-lipase aggregates are somewhat large but remain in a size range <10 nm.…”
Section: Resultsmentioning
confidence: 99%
“…For example, it has been reported that quercetin and epigallocatechin gallate (EGCG) act as pancreatic lipase inhibitors, binding to the enzyme near the active site [16,17]. Nevertheless, findings have suggested that flavonoids can form aggregates and that they are able to inhibit several unrelated enzymes [18,19]. McGovern et al (2003), have proposed that flavonoids can reversibly sequester some enzymes instead of binding to them in specific sites [20].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study suggests that the presence of flavonoid aggregates affects the reproducibility of pancreatic lipase assays [18], but their mechanism of action as aggregates is still unknown. Since it is likely that the ingested flavonoids are present in the human digestive track as aggregates, we hypothesize that the interaction with pancreatic lipase follows an additional mechanism besides molecular inhibition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation